The Opioid/Overdose Crisis as a Dialectics of Pain, Despair, and One-Sided Struggle - Friedman, Samuel R.; Krawczyk, Noa; Perlman, David C.; Mateu-Gelabert, Pedro; Ompad, Danielle C.; Hamilton, Leah; Nikolopoulos, Georgios; Guarino, Honoria; Cerdá, Magdalena (Frontiers in Public Health, 2020)
The opioid/overdose outbreak in the United States and Canada has claimed hundreds of thousands of lives and has become a major field for research and interventions. It has embroiled pharmaceutical companies in lawsuits and possible bankruptcy filings. Effective interventions and policies towards this and future drug-related outbreaks may be improved by understanding the sociostructural roots of this outbreak. Much of the literature on roots of the opioid/overdose outbreak focuses on 1. the actions of pharmaceutical companies in inappropriately, promoting the use of prescription opioids; 2. on “deaths of despair” based on the deindustrialization of much of rural and urban Canada and the United States, and on the related marginalization and demoralization of those facing lifetimes of joblessness or precarious employment in poorly paid, often dangerous work. A third major contributor to this outbreak has been less discussed: The probable increase in occupationally-induced pain and injuries in the population. Although findings about trends in pain have been contested, considerable evidence indicates an increase in the prevalence of pain. Research also finds that people employed in occupations and industries where occupationally-caused pain is more common contribute disproportionately to the population experiencing opioid-related fatal overdose. All three of these roots of the outbreak—pharmaceutical misconduct and unethical marketing practices, despair based on deindustrialization and increased occupational pain—can be traced back, in part, to what has been called the “one-sided class war” that became prominent in the 1970s, became institutionalized as neo-liberalism in and since the 1980s, and may now be beginning to be challenged. We describe this one-sided class war, and how processes it sparked enabled pharmaceutical corporations in their misconduct, nurtured individualistic ideologies that fed into despair and drug use, and reduced barriers against injuries and other occupational pain at workplaces by reducing unionization, weakening surviving unions, and weakening the enforcement of rules about workplace safety and health. We will then briefly discuss the implications of this analysis for programs and policies to mitigate or reverse the opioid/overdose outbreak.